Celebrating Danny Duncan's Birthday - Watkins, Howard::::::::: (1985)
Leslie Prusia presenting Danny award winning artist drawing of Fresno skyline and Sierras; also seated ?and Robin Watkins Location: Watkins dining room with remodeled kitchen in background